Pengaruh Komunikasi Layanan terhadap Minat Penggunaan Layanan Holistic Homecare for Elderly: Peran Mediasi Kepercayaan Pelanggan - Wiranto Wiranto; Lucia Diyah Reny P; Yessy Apriantriarta Cahya P; Yuni Fitria (Kajian Administrasi Publik dan ilmu Komunikasi, 2026)
Purpose: This study examines the effect of service communication on usage intention of Holistic Homecare for Elderly services, with customer trust serving as a mediating variable. Design/Methodology/Approach: Employing a quantitative explanatory approach with cross-sectional survey design, this research involved 120 family respondents with elderly members (≥60 years) in urban areas of Jakarta and Bandung, selected through stratified purposive sampling. Data were collected using structured questionnaires with 5-point Likert scales that had been tested for validity (Pearson correlation > 0.30) and reliability (Cronbach's Alpha > 0.70). Data analysis utilized Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 to examine measurement and structural models, along with bootstrapping mediation tests. Findings: Service communication demonstrated significant positive effects on customer trust (β = 0.712; t = 12.456; p < 0.001) and usage intention (β = 0.324; t = 4.213; p < 0.001). Customer trust significantly influenced usage intention (β = 0.498; t = 6.847; p < 0.001) and functioned as a partial mediator (indirect effect = 0.354; BootCI [0.248; 0.471]). Originality/Value: This research integrates Commitment-Trust Theory and Social Support Theory within the context of home-based elderly care services in a developing country, revealing the critical role of empathetic, responsive, and transparent communication as the foundation for trust-building that subsequently drives service adoption. Practical Implications: The findings emphasize the necessity of therapeutic communication training for caregivers and information transparency to establish a trustworthy homecare service ecosystem in Indonesia.